CHARACTERIZATION OF THE LEVEL OF ANXIETY OF NURSING STAFF DEPENDING ON THE SPECIFICS OF WORKING CONDITIONS - Marta Kachmarska; Lidiya Lyubinets; Elzbieta Cipora; Galyna Shveda (Acta Medica Leopoliensia)
Military events on the territory of Ukraine have acted as a factor influencing the state of mental health of the population. At the same time, healthcare professionals who provide medical care to the population, including the military, play an important role, which requires an assessment of their psychological state to ensure the proper quality of medical services.